2019
DOI: 10.21276/irjps.2019.6.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Perception of Self Medication Behavior Use of Complementary Alternative Medicine (Cam) in Denpasar City

Abstract: Introduction: CAM use in the community for supporting therapy in the treatment of diseases the community depends on behavioral factors and can be measured using Methods: This research is cross-sectional study. The sample used in the study is around 97 peoples in Denpasar City. The data were collected between November analyzed by using by ordinal logistic test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
0
1
Order By: Relevance
“…The results of the perceived barrier study with the understanding of RUM show significant results. This result is different from research, which states that the perceived barrier does not affect a person's desire to use drugs and is more influenced by culture [31]. The findings of this study are confirmed by other studies that show the community 's willingness to use anything suitable because of the lack of access to knowledge and time and insufficient public access to health services [32].…”
Section: Discussioncontrasting
confidence: 84%
“…The results of the perceived barrier study with the understanding of RUM show significant results. This result is different from research, which states that the perceived barrier does not affect a person's desire to use drugs and is more influenced by culture [31]. The findings of this study are confirmed by other studies that show the community 's willingness to use anything suitable because of the lack of access to knowledge and time and insufficient public access to health services [32].…”
Section: Discussioncontrasting
confidence: 84%